"It takes me a little longer to get angry now": Homeless children traumatised by family violence reflect on an animal therapy group. (11th February 2014) - Mudaly, Neerosh; Graham, Amanda; Lewis, Nerys
Abstract : Children who experience ongoing abuse, violence and homelessness often develop social, emotional, health and behavioural problems which are frequently manifested in trauma-based behaviours including self harming and suicidal behaviours, aggressive and criminal behaviours, and drug and alcohol problems. These children often do not engage with traditional therapeutic services. Their persistent fear associated with fleeing the violence and their subsequent transient living situations prevents them from engaging with professionals. An innovative therapeutic program using animals in an activity based group setting was implemented by a family violence housing and support agency to engage these children. As part of its commitment to improving responses to children this agency funded a preliminary, independent evaluation of the program. The objective of this evaluation was to obtain feedback from the children who had attended the group on their experiences of the animal therapy group. This paper reports on the children's views of the benefits of the group. ". . . .and when we're holding the animals, makes you feel more calmer and stuff" (13-year-old girl)